(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Because excessive growth of abnormal retinal vessels in the developing eye of the premature infant underlies retinopathy of prematurity (ROP), it may be hypothesized that a change in vascular endothelial growth factor (VEGF) level in the infant’s vascular bed predicts the course of the disease. Purpose: To determine serum VEGF levels and to assess changes in these levels over time in infants at risk for developing ROP. Materials and Methods: Twenty three infants born preterm underwent examinations for ROP. Two examinations were performed 14±3 days apart. A 1-ml blood sample was collected to obtain a 0.5-ml serum sample from each infant. Serum was frozen at -20° С until analysis. Serum VEGF levels were assessed by enzyme-linked immunosorbent assay (ELISA) method using Human VEGF-A ELISA Kit (Ray Biotech Inc., Norcross, GA) following the manufacturer’s instructions. Newborns were divided into two groups: those who exhibited ROP progression or absence of improvement (Group 1), and those who exhibited regression of ROP (Group 2). A Student’s t-test or Wilcoxon rank-sum test was used for two-group comparison. Results: There were no significant differences between groups with regard to birth weight or gestational age (p<0.17; p<0.06). In addition, there was no significant difference with regard to serum VEGF level between groups at the first and second screening examinations (p<0.56). The difference in serum VEGF levels between two screening examinations for Group 1 was not significant (Friedman test, p = 0.27), whereas a decrease in serum VEGF levels between these examinations for Group 2 was significant (Friedman test, p = 0.046). Conclusion: There was no significant difference with regard to serum VEGF level between groups at the first and second screening examinations. The increase in serum VEGF level between two examinations for infants who exhibited ROP progression or absence of improvement was not statistically significant. Infants with disease regression demonstrated a significant decrease in serum VEGF level at the second examination compared to the first examination.